BEHAVIORAL RESPONSE OF RAT TO N-HEXYL-METHYL KETONE AND DECANOIC ACID DERIVATIVES IDENTIFIED FROM ARMPIT GLAND SECRETION - Soundarapandian Kannan; Govindaraju Archunan; Ponnirul Ponmanickam (Tropical Life Sciences Research, 2007)
Armpit gland secretion from sexually mature and reproductively active male and female Rattus rattus (house rat), were analyzed by gas chromatography coupled mass spectrometry (GC-MS). Alkanes, aliphatic acids, esters and ketones were identified in the secretions. Four peaks were found to be higher concentration in male armpit gland which were identified as pentadecanoic acid 4,6,10,14 tetra methyl ester (I), decanoic acid (II), oleic acid (III) and decane 1,10 dibromo (IV) and where as the armpit gland of females three compounds viz., oleic acid (I), decane 1,10 dibromo (II) and n-hexyl-methyl ketone (III) were the major fractions. Odor preference test demonstrated that all the major chemical moieties identified in male armpit gland were found to attract both sexes. By contrast the III compound of female attracted conspecifics of the opposite sex, where compound I and II of females attracted both male and female individuals. The level of attraction also varied from compound to compound. The results conclude that the armpit gland of house rat contains five major fractions with pheromonal function in maintaining social behavior and reproductive status.